Cyperus Rotundus L. extract suppresses RANKL-induced osteoclastogenesis through NFATc1/c-fos downregulation and prevent bone loss in OVX-induced osteoporosis rat. (9th June 2017) - Kum, Chang-Jun; Kim, Eun-Young; Kim, Jae-Hyun; Lee, Bina; Min, Ju-Hee; Heo, Jun; Kim, Jong-Hyun; Yeom, Mijung; Sohn, Youngjoo; Jung, Hyuk-Sang
Abstract: Ethnopharmacological relevance: Cyperus Rotundus L. (CyR) has been widely used for the treatment of gynecologic disorder. Recent studies have reported that CyR can prevent the formation of cystic follicles and ovarian malfunction. However, the effects of CyR on osteoclastogenesis and postmenopausal osteoporosis remain unknown. Aim of the study: This study was aimed to investigate the preventive effects of CyR on RANKL-induced osteoclast formation and ovariectomy (OVX)-induced bone loss. Materials and methods: In this in vitro study, we investigate the anti-osteoporotic effect of CyR on receptor activator of nuclear factor kappa-B ligand (RANKL)-induced osteoclastogenesis, the formation of tartrate-resistant acid phosphatase (TRAP) multinucleated cells, pit formation, transcription factors such as NFATc1 and c-Fos, and mRNA expression of osteoclast-associated genes were investigated. Forty 12-weeks female Sprague-Dawley rats for in vivo effect of CyR were used and OVX rat model was determined. The rats were randomly assigned into sham group and four OVX groups, i.e. OVX with D.W; OVX with estradiol (E2, 100 μg/kg/day), OVX with CyR-L (16 mg/kg/day), OVX with CyR-H (160 mg/kg/day). The treatment lasted for 8weeks. Results: CyR inhibited osteoclast differentiation and pit formation in the RANKL-induced osteoclastogenesis of RAW 264.7 cells. Reverse transcription polymerase chain reaction analysis also showed that CyR reduced the mRNA expression of osteoclast-associated genes such as carbonic anhydrase II, TRAP, RANK, cathepsin K, matrix metalloproteinase 9, nuclear factor of activated T cells cytoplasmic 1 (NFATc1), and c-Fos. In addition, CyR decreased protein levels of NFATc1 and c-Fos. CyR inhibited trabecular bone loss in the femur caused by OVX. Conclusion: The results of this study indicate that CyR inhibits the RANKL-induced osteoclast differentiation in RAW 264.7 cells and trabecular bone loss in OVX rats. Graphical abstract: